Engaging Secondary School EFL Students in Speaking Classroom through Guessing Games - Zhafirah Alifah Yumna; Sidik Indra Nugraha; Yousef Bani Ahmad (Journal of Educational Sciences, 2026)
Speaking remains one of the most challenging skills for EFL learners, particularly in contexts where classroom interaction is limited. To address this issue, interactive techniques such as Guessing Games are widely considered effective for promoting learner participation. This study aims to investigate students’ engagement in an EFL speaking classroom through the use of Guessing Games and to explore their perceptions of its implementation. Employing a qualitative descriptive design, the research was conducted in a secondary senior high school in Karawang Regency, West Java, Indonesia, involving one intact class of 30 eleventh-grade students aged 16–17. Data were collected through semi-structured interviews and classroom observation checklists, and analyzed using data condensation, data display, and conclusion drawing. The findings indicate that students demonstrated strong behavioral, emotional, and cognitive engagement during the learning process. They followed classroom rules, listened attentively, and maintained focus; expressed enthusiasm, enjoyment, and positive emotions; and showed cognitive growth by enhancing their vocabulary, applying critical thinking, and demonstrating creativity when describing objects. Additionally, the activity fostered stronger peer and teacher–student connections. In conclusion, Guessing Games effectively support a more interactive, motivating, and engaging speaking classroom, making them a valuable technique for EFL instruction.